A3_7 Pandora’s Floating Mountains: Lagrange Point - McQuade, Gregor; Garland, Lee; Walker, Michael; Bradley, Thomas (Physics Special Topics, 2014)
This article investigates the physical possibility of the floating mountains depicted in the film “Avatar”. It was theorised that should the L1 Lagrange point between the moon the movie was based on, and the gas giant it is shown to orbit lie on the surface of the planet, then any matter at that point should float. It was found that the planet would have to orbit very closely to the gas giant, within 0.6247 planetary radii of the surface, and would therefore be unfeasible in the manner depicted in the movie due to the natural disasters this would incur.